Evaluación de las propiedades mecánicas y físicas de elementos de madera plástica en diferentes dosificaciones de polímeros reciclados. (2020)
MAPLECO SAS, (Ecological Plastic Wood), is a company from Boyacá that, for more than 5 years in the plastic reuse sector, manufactures elements 100% with raw material from different cooperatives in the sector and some from Bogotá, which carry their material to the municipality of Ventaquemada where the factory is located. The degree work consisted fundamentally of carrying out physical and mechanical tests on 20x10x2.5 cm plastic wooden tablets, with 5 different mixtures of dosages certified by Mapleco S.A.S. Density, absorption, flexo-traction and aging tests were carried out. From the results of the analyzed properties, it is concluded that plastic wood has a very low absorption percentage, which makes it resistant to aggressive environmental conditions. As for the calculated Modulus of Break, it shows a high resistance compared to conventional materials. Although it is necessary to continue investigating other properties of plastic wood, the foregoing indicates that it can become an alternative material to concrete and clay in the manufacture of paving stones, contributing to sustainability within the construction of articulated pavements.